STRUKTUR GENETIK DAN FILOGENI YELLOWFIN TUNA (THUNNUS ALBACARES) BERDASARKAN SEKUEN DNA MITKONDRIA CONTROL REGION SITOKROM OKSIDASE I PADA DIVERSITAS ZONE BIOGEOGRAFI - I Made Sara Wijana; I Gusti Ngurah Mahardika (Environmental Research Center (PPLH) of Udayana University, 2010)
Genetic structure and phylogeni of 37 sequences control region DNA mitochondrial cytocrome oxidase I of yellowfin tuna (Thunnus albacores) have been downloaded from GeneBank and analised using Maximum Likehood (ML), Pairwise Genetic Distance and Bootstrapping Phylogeni Model of Kimura 2 Parameter. The result shows that the corrected value of the data was 5,5% and the mean of genetic distances was 3,7 %, where the shortest distance was 0.0% and the longest was 5%. The genetic distances with the out group (Thunnus obesus) ranged between 7,8 % – 9,8 % and with the Thunnus thynus ranged between 10,4% – 12,5%. The value of bootstrap phylogeny of 37 sequences of yellowfin tuna was less than 50%. All those results shows that there was no significant genetic differences of 34 samples sourced from Philipines and 3 from Spain based on sequence region DNA mitochondrial cytocrome oxidase I.